STUDIES ON THE FACTORS INFLUENCING SPAWNING OF INDIAN MAJOR CARPS IN 'BUNDH' FISHERIES - Saha, K C; Sen, D P; Roy Chowdhury, A K; Chakravarty, S K (Indian Journal of Fisheries, 2015)
Indian major carps like Rohu (Labeo rohita), Catla (Catla catla) and Mrigal (Cirrhina mrigala) are known to be very shy to breed in confined waters and this is why the carp culturists of West Bengal are to depend largely for their spawn supplies on riverine areas. Casual attempts, made by some of the workers for making the carps yield to artificial breeding through stripping process did not give desired results unlike the common European carp (Cyprinus carpio) which has become so domesticated that it yields to spawning under entirely artificial conditions. There are, however, certain confined waters which are locally known as Bundhs, having large catchment areas which get flooded by rain-waters, creating conditions favourable for spawning of Indian major carps. These Bundhs are mostly localized in the Districts of Bankura and Midnapore in West Bengal.